Clinical Outcome of Conservative Management of Acute Appendicitis - Bukhari, Syeda Midhat Fatima; Khan, Taufeeq Ahmed; Aamir, Muhammad Uzair; Ghalib, Atiqa; Chudary, Muhammad Amjad; Shehzad, Muhammad; Rind, Muhammad Aqib (Biological and Clinical Sciences Research Journal, 2025)
Conservative management of uncomplicated acute appendicitis using antibiotics has gained global interest as a safe alternative to surgery. This approach is especially relevant in resource-limited healthcare systems like Pakistan, where surgical capacity and accessibility remain constrained. This study aimed to evaluate the clinical outcomes of non-operative management in patients with uncomplicated acute appendicitis in a Pakistani tertiary care setting. Methods: This prospective observational study was conducted at a PIMS hospital in Islamabad from 9 November 2024 to 9 February 2025. Patients were treated conservatively with intravenous antibiotics followed by oral antibiotics. Primary outcomes included symptom resolution, recurrence within six months, and the need for delayed appendectomy. Secondary outcomes included hospital stay duration, complications, and readmission rates. Data were analyzed using SPSS version 26.0. Results: Symptom resolution was achieved in 86.2% of patients within 48 hours. During initial admission, 94.3% were successfully managed without surgery. At six-month follow-up, 80.5% remained symptom-free. In 13.8% of patients, recurrence occurred, while 11.5% required delayed appendectomy. Complication and readmission rates were low (3.4% and 6.9%, respectively), and the mean hospital stay was 3.8 days. Conclusion: Conservative management of uncomplicated acute appendicitis is a safe and effective alternative to surgery in selected patients. This approach may reduce hospital burden, lower healthcare costs, and minimize surgical risks in the Pakistani healthcare context.